A New Application of Homotopy Analysis Method: Mojtaba Ghanbari, Tofigh Allahviranloo - Team, Support (Thai Journal of Mathematics, 2012)
In this paper, we focus on linear fuzzy Fredholm integral equations of the second kind and propose a new method for solving it, namely “homotopy analysis method” (HAM). It is found that the HAM provides us with a simple way to adjust and control the convergence region of solution series by introducing an auxiliary parameter h. The results illustrate the validity and the great potential of the HAM in solving fuzzy integral equations.